The investigation of some bioactive compounds and antioxidant properties of hawthorn (Crataegus monogyna subsp. monogyna Jacq) - Keser, Serhat; Celik, Sait; Turkoglu, Semra; Yilmaz, Okkes; Turkoglu, Ismail (Scopemed, 2014)
The antioxidant and pharmacological effects of hawthorn have mainly been attributed to the polyphenolic contents. The aim of this research is to determine some bioactive compounds and antioxidant properties of hawthorn aqueous and ethanol extracts of leaves, flowers, and ripened fruits. Materials and Methods: For this purpose, antioxidant activities of extracts were assessed on DPPH center dot, ABTS center dot +, superoxide scavenging, reducing power and ferrous metal chelating activity assays and phenolic content of extracts was determined by Folin-Cioacalteu's reagent. Results: The flavonoids including rutin, apigenin, myricetin, quercetin, naringenin and kaempferol, were identified by high- performance liquid chromatography in the hawthorn extract. Conclusion: It was observed the aqueous and ethanol extracts of Crataegus monogyna subsp. monogyna fruits showed the highest activity in reducing power and metal chelating activity assays. In addition, it was determined that the aqueous flower extract showed higher flavonoid content than aqueous leaves extract. The antioxidant and pharmacological effects of hawthorn have mainly been attributed to the polyphenolic contents.
Keywords: Antioxidant activity; Crataegus monogyna subsp. monogyna; flavonoid; polyphenolic content